Determinants of the Application of Handwashing with Soap in the Elderly in Preventing Covid-19 at UPT PSTW Khusnul Khotimah Riau Province Social Service in 2022: Determinan Penerapan Cuci Tangan Pakai Sabun Pada Lansia Dalam Pencegahan Covid-19 Di UPT PSTW Khusnul Khotimah Dinas Sosial Provinsi Riau Tahun 2022 - Ferda Melenina; Hetty Ismainar; Hayana Hayana; Zulmeliza Rasyid; Welly Sando (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Handwashing With Soap is as an implementation of sanitation that achieves optimal hygiene by washing hands and fingers using soap in running water, one of the purposes of Washing Hands With Soap is to avoid infections contaminated with viruses through the nose, mouth, and eye contact. Tresna Werdha Khusnul Khotimah Social Service Technical Service Unit is a Tresna Werdha Social Service Technical Service Unit under the auspices of the Riau Provincial Social Service Office. Tresna Werdha Khusnul Khotimah Social Service Technical Service Unit has 64 elderly people, there are 7 cases of covid-19 in it. The purpose of this study is generally to look at factors related to the application of handwashing with soap to the elderly in the prevention of covid-19. This type of research is quantitative by using cross sectional design. The study sample was 64 elderly using Total Sampling. The location of this study was at the Tresna Werdha Khusnul Khotimah Social Service Technical Service Unit in April-May 2022. The results showed that knowledge (P value = 0.006, OR = 4,948), attitude (P value = 0.011, OR = 4,385), action (P value = 0.005, OR = 5,273), handwashing facilities with soap (P value = 0.035, OR = 3,438) means that there is a significant relationship with the application of handwashing with soap in the elderly in the prevention of Covid-19. It is recommended for the Social Service Technical Service Unit of Tresna Werdha Khusnul Khotimah to increase the application of washing tangsan with soap for the elderly by accompanying every activity to implement hand washing and providing campaign / educational media such as banners / posters regarding the application of handwashing with soap in the prevention of Covid-19.